Temporal Patterns of Novel Circulating Biomarkers in IL-2-mediated Vascular Injury in the Rat. (October 2015) - Keirstead, Natalie D.; Bertinetti-Lapatki, Cristina; Knapp, Denise; Albassam, Mudher; Hughes, Valerie; Hong, Feng; Roth, Adrian B.; Mikaelian, Igor
Recombinant interleukin-2 (rIL-2) administration in oncology indications is hampered by vascular toxicity, which presents as a vascular leak syndrome. We used this aspect of the toxicity of rIL-2 to evaluate candidate biomarkers of drug-induced vascular injury (DIVI) in rats given 0.36 mg/kg rIL-2 daily. Groups of rats were given either 2 or 5 doses of rIL-2 or 5 doses of rIL-2 followed by a 7-day recovery. The histomorphologic lexicon and grading scheme developed by the Vascular Injury Working Group of the Predictive Safety Testing Consortium of the Critical Path Institute were utilized to enable semiquantitative integration with circulating biomarker levels. The administration of rIL-2 was associated with time-dependent endothelial cell hyperplasia and hypertrophy and perivascular inflammation that correlated with increases in circulating angiopoietin-2, lipocalin-2, monocyte chemotactic protein-1, tissue inhibitor of metalloproteinase-1, vascular endothelial growth factor A, E-selectin, and chemokine (C-X-C motif) ligand-1, and the microRNAs miR-21, miR-132, and miR-155. The dose groups were differentially identified by panels comprising novel candidate biomarkers and traditional hematologic parameters. These results identify biomarkers of the early stages of DIVI prior to the onset of vascular smooth muscle necrosis.